Mobile application: Learning basic mathematics operation using augmented reality / Nur Hasni Nasrudin ... [et al.] - Nasrudin, Nur Hasni; Mohamad Hatta, Mohamad Harith Azfar; Azmi, Anis Zafirah; Ahmad Junid, Rosida (Universiti Teknologi MARA, Perak, 2021)
At school, students must learn mathematics not only as a formality to participate in exams, but also to use their mathematical knowledge to solve problems in their daily lives. When students deal with numerical information, they tend to have negative feelings or fear, and this is known as mathematical anxiety. The project aims to develop a mobile application that integrates augmented reality technology into mathematical education and to evaluate the technical acceptance of the mobile application. This mobile application is reviewed and tested by 23 end users, most of whom are educators and parents. By using Technology Acceptance Model (TAM), three attributes were measured. The attributes include perceived as useful, user-friendly, and intended for use. Based on the results, it can be concluded that the educators and parents are satisfied with the mobile application. For future work, the research recommends adding a variety of exercises with diversifying forms of questions with answers in the mobile application. It is further recommended that the augmented reality output implement a 3D modeling design to project better virtual images.